Cambio técnico y política económica: la teoría y el caso colombiano (1950 - 2019) (2020)
The right policy to economic growth is based on the theory of a decentralized (market) society whose productive activity expands in the long term amid ups and downs thanks to technical change and the emergence, time and again, of various obstacles to economic growth. In the Colombian case of the last 70 years, the rates of economic growth and technical change have been associated with the inter-sectoral mobilization of productive resources, that is, to what is called “structural change”, and this, in turn, to economic policies (sometimes no so right)